NALISIS PENGARUH TINGKAT PENGANGGURAN DAN RASIO KETERGANTUNGAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TENGAH TAHUN 2001-2017 - Dewiaulia Adi Sukma; Lucia Rita Indrawati; Whinarko Juliprijanto (Universitas Tidar, 2020)
This study aims to determine and analyze the effect of the Unemployment Rate andthe Ratio of the Burden of Dependence to Economic Growth in Central Java Province.This study uses time series data from 2001 to 2017. The data collection methods used werelibrary research methods obtained from BPS (Central Statistics Agency) in Central Javaand BPS (Central Bureau of Statistics) Indonesia. The data analysis technique usesmultiple regression methods and classical assumption tests. The results of this studyindicate that: (1) there is a significant influence between the variable unemployment rateon the variable economic growth. (2) there is a significant effect between the variable loadratio dependence on economic growth variables. (3) Variable unemployment rates anddependency expense ratios jointly have a significant effect on economic growth variablesin Central Java province in 2001-2017.